Gender differences in awareness and practices of cancer prevention recommendations in Korea: a cross-sectional survey - Yoonjoo Choi; Naeun Kim; Jin-Kyoung Oh; Yoon-Jung Choi; Bohyun Park; Byungmi Kim (Epidemiology and Health)
OBJECTIVES Gender is a major determinant of health behaviors that influences cancer prevention awareness and practices. This study investigated the relationship of the awareness and practice rates of cancer prevention recommendations with gender and socioeconomic status. METHODS We used data from the Korean National Cancer Prevention Awareness and Practice Survey (2023). The sample included 4,000 men and women aged 20-74 years. We conducted multiple logistic regression analyses to evaluate associations with the awareness and practices of cancer prevention, and a joinpoint regression analysis using age-standardized rates to analyze trends in awareness and practice rates from 2007 to 2023. RESULTS The awareness rates were 79.4% and 81.2% for men and women, respectively. The overall practice rates were substantially lower (43.1% for men and 48.9% for women). For men, awareness rates did not differ significantly by socio-demographic characteristics, but practice rates increased with age (20-29: 15.9%; 60-74: 53.8%). For women, both awareness (20-29: 73.0%; 60-74: 85.7%) and practice (20-29: 16.8%; 60-74: 67.5%) rates increased with age. The easiest recommendations to follow were “reducing salt intake and avoiding burnt or charred foods” (men: 29.9%; women: 28.4%), whereas the most difficult recommendation was “engaging in regular physical activity” (men: 32.5%; women: 34.4%). CONCLUSIONS While awareness of cancer prevention recommendations was high, the practice of these recommendations was low. Gender influenced changes in awareness and practice rates over time, reflecting a large gap in practice. Future research should explore appropriate intervention points for cancer prevention practices and the development of more effective cancer prevention policies.